2022
DOI: 10.3389/fneur.2022.884770
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mechanism of Acupuncture Treatment of Chronic Pain: An Individual-Level Positron Emission Tomography Study

Abstract: ObjectiveAcupuncture has been shown to be effective in the treatment of chronic pain. However, their neural mechanism underlying the effective acupuncture response to chronic pain is still unclear. We investigated whether metabolic patterns in the pain matrix network might predict acupuncture therapy responses in patients with primary dysmenorrhea (PDM) using a machine-learning-based multivariate pattern analysis (MVPA) on positron emission tomography data (PET).MethodsForty-two patients with PDM were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Liu et al [17] used the Least Absolute Shrinkage and Selection Algorithm (LASSO) to integrate sample salient features in order to construct support vector machine models. while Xu et al [27] showed a non-significant traditional mass univariate correlation between brain metabolism and altered pain intensity. Another study by Yu et al [28] applied the multivariate pattern analysis (MVPA) method of SVM to further optimize the prediction of the efficacy of acupuncture for primary dysmenorrhea (PDM) patients.③Most current predictions of acupuncture efficacy use subjective symptoms as labels, and thus the validity of the labels is influenced by individual cognitive biases, leading to heterogeneity of results.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al [17] used the Least Absolute Shrinkage and Selection Algorithm (LASSO) to integrate sample salient features in order to construct support vector machine models. while Xu et al [27] showed a non-significant traditional mass univariate correlation between brain metabolism and altered pain intensity. Another study by Yu et al [28] applied the multivariate pattern analysis (MVPA) method of SVM to further optimize the prediction of the efficacy of acupuncture for primary dysmenorrhea (PDM) patients.③Most current predictions of acupuncture efficacy use subjective symptoms as labels, and thus the validity of the labels is influenced by individual cognitive biases, leading to heterogeneity of results.…”
Section: Discussionmentioning
confidence: 97%